2021
DOI: 10.1080/00325481.2021.1987732
|View full text |Cite
|
Sign up to set email alerts
|

The clinical course and short-term health outcomes of multisystem inflammatory syndrome in children in the single pediatric rheumatology center

Abstract: Objectives Multisystem inflammatory syndrome in children (MIS-C) is a rare but severe condition resulting in excessive response of the immune system after SARS-CoV-2 infection. We report a single-center cohort of children with MIS-C, describing the spectrum of presentation, therapies, clinical course, and short-term outcomes. Methods This is a prospective observational study from to a tertiary pediatric rheumatology center including patients (aged 1 month to 21 years) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
19
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 47 publications
4
19
6
Order By: Relevance
“…In our study, gastro-intestinal symptoms were observed in 50.37% cases, which was lower than that reported in other studies ( 13 , 25 , 26 ) but more than the Latin American study ( 24 ). The figure is still much lesser than that reported in the systematic review (85.6%) ( 12 ), which may be because of a larger sample size in the later.…”
Section: Discussioncontrasting
confidence: 85%
See 4 more Smart Citations
“…In our study, gastro-intestinal symptoms were observed in 50.37% cases, which was lower than that reported in other studies ( 13 , 25 , 26 ) but more than the Latin American study ( 24 ). The figure is still much lesser than that reported in the systematic review (85.6%) ( 12 ), which may be because of a larger sample size in the later.…”
Section: Discussioncontrasting
confidence: 85%
“…This is in agreement with the epidemiology of MIS-C, which indicates that majority of the cases develop 4–6 weeks after exposure to the virus ( 27 ). In our study, 23.9% had underlying co-morbidities, whereas it was 38.7% in the previous Indian study ( 13 ), 28.35% in Turkish study ( 26 ), and 15.8% in the Latin American study ( 24 ).…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations